Terminology in specialized fields: structure, challenges, and implications - Panjiyeva Ro’zixol (Euro Asian Journal Publishing, 2024)
Terminology is critical in ensuring precise and unambiguous communication within specialized fields such as medicine, law, and technology. This paper investigates the structure of terminology, explores the challenges in standardizing and managing terms, and discusses the implications of effective terminology use.
Keywords: Terminology; specialized field; standardization